A METHODOLOGICAL FRAMEWORK FOR VISUAL COMFORT ASSESSMENT IN EDUCATIONAL SPACES - Hazim Seder; Janani Selvam; Najib Al-Ashwal (Universitas Malikussaleh, 2026)
Visual comfort is a critical component of indoor environmental quality in schools, where lighting conditions influence visual performance, attention, and perceived well-being. In dense urban fabrics and semi-arid climates, classrooms often face a dual constraint: limited effective daylight use due to glare, privacy, and noise, alongside over-reliance on inadequately tuned electric lighting. This paper proposes a structured methodological framework for assessing visual comfort through an integrated workflow that combines field-based diagnostics (spot illuminance measurements and photographic documentation), occupant feedback, and simulation-based illustration using DIALux Evo. An illustrative, case-based application in public schools in Hebron City (Palestine) demonstrates how the framework supports interpretive understanding of recurring conditions, such as uneven illuminance distribution and potential glare-related situations, using standards (e.g., EN 12464-1) as non-evaluative reference points. The study does not claim performance compliance, certification, or predictive validation. It outlines how AI-assisted decision support may be incorporated in future work to enable scalable early-stage assessments across classroom typologies.